2024
DOI: 10.1002/solr.202300961
|View full text |Cite
|
Sign up to set email alerts
|

2D Polymers with Lead Anchoring Groups Enable Perovskite Solar Cells with Over 24% Efficiency

Hongtao Lai,
Xingchen Tang,
Leyu Bi
et al.

Abstract: The hygroscopic dopants used in Spiro‐OMeTAD hole‐transport materials (HTMs) in n–i–p perovskite solar cells (PSCs) inevitably cause device degradation. Herein, two polymer interface materials based on lead anchoring groups are developed. It is found that 2D polymers 2DP‐BT and 2DP‐Por can form dense films and exhibit excellent hydrophobicity. Importantly, 2DP‐Por can passivate the surface defects through noncovalent interactions, reducing nonradiative recombination loss. After introducing these polymer interf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…It was found that the HI of devices significantly decreased from 0.116 to 0.065 after p­(HEMA- co -DEAMA) modification, indicating reduced channels for ion migration. The integrated J SC values were 23.01 and 23.69 mA/cm 2 for the control and p­(HEMA- co -DEAMA)-modified devices via external quantum efficiency (EQE) spectra (Figure b), which roughly matches the data extracted from the J–V curves . To evaluate the effect of p­(HEMA- co -DEAMA) doping on the overall optical stability of the device, we further tracked the PCE of the corresponding devices in the steady-state at the point of maximum power.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that the HI of devices significantly decreased from 0.116 to 0.065 after p­(HEMA- co -DEAMA) modification, indicating reduced channels for ion migration. The integrated J SC values were 23.01 and 23.69 mA/cm 2 for the control and p­(HEMA- co -DEAMA)-modified devices via external quantum efficiency (EQE) spectra (Figure b), which roughly matches the data extracted from the J–V curves . To evaluate the effect of p­(HEMA- co -DEAMA) doping on the overall optical stability of the device, we further tracked the PCE of the corresponding devices in the steady-state at the point of maximum power.…”
Section: Resultsmentioning
confidence: 99%
“…The integrated J SC values were 23.01 and 23.69 mA/cm 2 for the control and p(HEMA-co-DEAMA)modified devices via external quantum efficiency (EQE) spectra (Figure 5b), which roughly matches the data extracted from the J−V curves. 30 To evaluate the effect of p(HEMA-co-DEAMA) doping on the overall optical stability of the device, we further tracked the PCE of the corresponding devices in the steady-state at the point of maximum power. As displayed in Figure 5c, the steady-state PCE of the unmodified device was only 19.40% with a constant bias of 0.83 V, and there was a significant attenuation after 250 s. For device doped with p(HEMA-co-DEAMA), the stabilized PCE is 20.80% with a constant bias voltage at 0.88 V. Most importantly, the device shows better optical stability with almost no attenuation within 250 s, revealing that the operational photovoltaic device is stable.…”
Section: Acsmentioning
confidence: 99%